1997
DOI: 10.1103/physrevlett.79.257
|View full text |Cite
|
Sign up to set email alerts
|

Non-Arrhenius Behavior of Surface Diffusion near a Phase Transition Boundary

Abstract: We study the non-Arrhenius behavior of surface diffusion near the second-order phase transition boundary of an adsorbate layer. In contrast to expectations based on macroscopic thermodynamic effects, we show that this behavior can be related to the average microscopic jump rate which in turn is determined by the waiting-time distribution W (t) of single-particle jumps at short times. At long times, W (t) yields a barrier that corresponds to the rate-limiting step in diffusion. The microscopic information in W … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 16 publications
3
20
0
Order By: Relevance
“…We find that E A extracted from the Arrhenius analysis is strongly temperature dependent, and seems to have a peak close to T /T M . A similar observation has been made in studies of adatoms diffusing on a solid substrate, where E A is found to have a maximum close to a secondorder phase boundary [48]. In our case, however, this behavior is not to be expected, since we do not cross any phase boundary but remain in the lo phase at all times.…”
Section: Lipid-cholesterol Mixturessupporting
confidence: 74%
“…We find that E A extracted from the Arrhenius analysis is strongly temperature dependent, and seems to have a peak close to T /T M . A similar observation has been made in studies of adatoms diffusing on a solid substrate, where E A is found to have a maximum close to a secondorder phase boundary [48]. In our case, however, this behavior is not to be expected, since we do not cross any phase boundary but remain in the lo phase at all times.…”
Section: Lipid-cholesterol Mixturessupporting
confidence: 74%
“…The only region where significant size effects and non-Arrhenius behavior for diffusion constant have been observed is near the critical region of a continuous phase transition. 19,20 This is due to the divergent correlation length in the critical region. In the present study, the transition temperature T c from the 1ϫ1 phase to the c(2ͱ2 ϫ4ͱ2)R45°is estimated to be at T c Ӎ100 K. Thus even the lowest temperature Tϭ176 K in the present study is quite well separated from the critical region.…”
Section: ͑52͒mentioning
confidence: 99%
“…3͑b͒ plots the residence-time distributions at 550 and 590 K. The distributions do not follow very closely a form of exponential decay, suggesting a site-specific activation energies 31 and/or nonArrhenius behavior. 32 However, there are not enough hops to extract statistically significant residence-time distributions for each site in our measurement.…”
Section: Resultsmentioning
confidence: 99%